Growth Stunting and Nutritional Deficiencies among Children and Adolescents with Celiac Disease in Kuwait: A Case-Control Study - Esraa Almahmoud; Dalal Usamah Zaid Alkazemi; Wafaa Al-Qabandi (MDPI AG, 2024)
Background/Objectives: This study aimed to assess the nutritional status of children and adolescents with celiac disease (CD) in Kuwait and investigate the nutritional deficiencies and sociodemographic factors associated with growth stunting in this population. Methods: This case-control study included 77 CD patients aged 3-18 years diagnosed with CD using IgA anti-tissue transglutaminase and duodenal biopsy and 33 healthy controls. Nutritional status was evaluated based on demographic and clinical characteristics, anthropometric measurements, and biochemical parameters. Univariate and multivariate logistic regression models were used to determine the association between CD and growth stunting. Results: Approximately one-third (31%) of children with CD had stunted growth, 20.8% had a low body mass index for their age, and 5.2% had both growth stunting and wasting. Children with CD had higher odds of iron-deficiency anemia, vitamin D deficiency, anemia, and lower socioeconomic status. They were also younger and had decreased serum levels of vitamin D compared to the controls. These factors were all significantly associated with an increased risk of CD, collectively explaining over 50% of the risk. For growth stunting, lower education status among mothers, family income, and serum ferritin were identified as risk factors. Conclusions: A significant proportion of children and adolescents with CD had malnutrition, overt deficiencies, and impaired growth despite coherence with a gluten-free diet. Recommendation: Routine monitoring and targeted nutritional interventions are recommended for children and adolescents with CD to address malnutrition and growth stunting. Addressing socioeconomic disparities and enhancing maternal education may also help mitigate the risk factors.